Trends in the market for drug delivery devices categorized as combination drugs and medical devices and regulatory challenges for autoinjectors in Japan - Mochizuki, Makiko; Maeda, Hideki (Frontiers in Medical Technology, 2024)
Background: Although a variety of drug delivery devices have been launched in recent years, few studies have comprehensively investigated the market trends of combination drugs and medical devices approved or certified in Japan and the regulatory challenges related to their approval. Among the drug delivery devices, autoinjectors are more convenient than traditional prefilled syringes and are designed with safety features to prevent needlestick accidents, allowing self-injection by patients. Therefore, autoinjectors have been incorporated into the treatment of various diseases and have shown significant growth among drug delivery devices.Aim: This study aimed to investigate the market trends of combination drugs approved in Japan, especially those with autoinjector formulations, and to explore the challenges in the regulatory aspects of combination drugs.Methods: Information on the number of marketed drugs and medical devices was obtained from the Pharmaceuticals and Medical Devices Agency (PMDA) database using specific definitions. We looked at the annual changes in the number of drug delivery devices approved and certified as combination drugs or medical devices and the number of canceled certifications. We also examined the classification and main certification criteria for Japanese medical device nomenclature.The study suggested that the number of combination drugs with autoinjector formulations is increasing, replacing previously approved or certified pen-type medication injectors. Moreover, 53% of all drug products were approved for autoinjector formulations after the initial authorization approval in Japan, and more than half of them obtained approval for additional formulations for autoinjectors within five years of the initial authorization approval, with the largest number of cases obtaining approval for additional formulations two years later. Conclusion: The lack of clear regulatory requirements for autoinjectors may lead to confusion among applicants. Furthermore, there are challenges in filing regulatory applications, thus hindering the rapid launch of combination drug-utilizing devices with superior usability.